A Comprehensive Review on Cluster based Energy Efficient Routing Protocols in Wireless Sensor Networks - Nivedhitha, V; Saminathan, A. Gopi (International Journal of Computer Sciences and Engineering, 2025)
Recent technological advancements like internet of things, home automation, disaster management etc shed light on wireless sensor networks. Thousands of micro sensor nodes are geographically located to capture a remote environment. The communication and computing process consume more energy from the nodes. Prolong usage of same path to transfer data may lead to decrease of the residual energy in the sensor nodes, thus causes the node to death. Power conservation in the nodes is the major concern in hostile environments. Clustering is an energy saving scheme that enables the nodes to communicate data to the nominated cluster heads, from where the cluster heads communicate the gathered data to the sink. This gain focus on two factors of increasing the node life time, namely - the selection of cluster head that has more residual energy and the periodic change of cluster heads. This paper surveys on various energy-aware clustering schemes involved in routing data from the sensor nodes to sink.